Effect of Landscape Composition and Habitat Conditions on the Diversity of Predatory Insects (Spiders, Ants, and Ground Beetles) in Cabbage Fields - Syahputra, Arif firman; Rizali, Akhmad; Hadi, Mochamad Syamsul (Research Journal of Life Science, 2024)
In a landscape, various types of land use compositions and different habitat conditions can affect the diversity and abundance of living organisms, particularly predatory insects. The observed landscape is a cabbage plantation area located in the highlands, featuring diverse habitat conditions, vegetation variations, and surrounding land use compositions such as agriculture, natural habitats, industrial areas, and settlements. This study aims to determine the diversity and abundance of predators, particularly spiders, ants, and ground beetles, in cabbage farming, influenced by differences in landscape composition and habitat conditions in the Malang and Pasuruan districts. Landscape analysis was conducted through direct checking (ground survey), followed by digitization using QGIS software, and data analysis was performed using the RStudio application. Plant age did not affect the diversity and abundance of predatory insects in cabbage plants. Elevation was related to the abundance of ants, as well as the diversity and abundance of ground beetles. The use of insecticides had no relationship with the diversity and abundance of predatory insects. Almost all land use compositions around the study area significantly impacted the diversity and abundance of predators. Therefore, it can be concluded that certain habitat conditions and landscape compositions are related to the diversity and abundance of predatory insects in cabbage plants.